Propuesta de mejora de la gestión logística de abastecimiento en la Constructora Equilátero Proyectos en Bogotá, Colombia (2021)
According to the information provided by the company Equilátero Proyectos, an analysis of the supply logistics is carried out. For this purpose, an analysis of the operation of the logistics operation will be prepared, from the selection of suppliers, storage of the material and its exit, all this, starting from a diagram in which the processes and clients will be considered; and with the help of value stream mapping the process is characterized.